Sistem Informasi Pengelolaan Anggaran Berbasis Web Di Kepolisian Resort Karanganyar - Ana Putri, Febrika Melly (Indonesian Journal of Information Technology and Computing (IMAGING), 2025)
Polres Karanganyar is one of the government institutions responsible for budget management in the implementation of activities within its agency. Budget management at Polres Karanganyar is still conducted manually, resulting in complexity, limitations, a lack of transparency, and difficulties in budget reporting and decision-making. The manual system leads to the potential for errors, delays, and the risk of budget misuse, as well as hindering efficiency and accountability in budget management. Given these issues, the development of a web-based budget management information system becomes crucial to enhance efficiency, accuracy, transparency, and decision-making capabilities in Polres Karanganyar regarding budget utilization. The information system developed by the author uses the SDLC (System Development Life Cycle) method, employing PHP programming language and MySQL database. The objective of this research is to develop an efficient, transparent, and accountable budget management information system at Karanganyar Police Resort. The result of this research is a web-based budget management information system. With the web-based information system, it is expected that users can easily manage, monitor, and report budgets, as well as expedite decision-making processes related to budget allocation. Keywords: Information Systems, budget, web, php, mysql